Microwave treatment of electric arc furnace dust with Tetrabromobisphenol A: Dielectric characterization and pyrolysis-leaching - Al-Harahsheh, Mohammad; Kingman, S.W.; Hamilton, Ian S. (Elsevier, 2017)
In the present work microwave treatment of electric arc furnace dust (EAFD) mixed with tetrabromobisphenol A (TBBPA) was investigated. A range of characterization techniques were used to understand the thermal behaviour of TBBPA-EAFD mixtures under microwave pyrolysis conditions. Dielectric and thermal properties of EAFD, TBBPA and their mixtures were determined. Both the dielectric constant and loss factor of the mixture were found to vary considerably with temperature and subsequently it was found that the mixtures of these materials absorbed microwaves effectively, especially at temperatures above 170 °C. The high loss tangent of EAFD-TBBPA mixture above 170 °C resulted in fast heating and high temperatures (above 700 °C) resulting in reduction of Fe, Pb and Zn to their metallic form. This resulted in low recoveries of both Zn and Pb when the residue was leached in water. The recovery of Zn varied between 14 and 52 wt,%, while Pb recovery varied between 3 and 31 wt.% depending on microwave treatment efficiency. The low recovery of Zn and Pb could be ascribed by the reduction of metal oxides into their metallic form. More importantly this work has shown great selectivity in the leachability of both zinc and iron; with iron being left in the solid residue.